Selected issues of municipal waste management in the context of implementing the concept of sustainable development - Gwarda, Karolina (Wybrane problemy gospodarki odpadami komunalnymi w kontekście realizacji koncepcji zrównoważonego rozwoju, 2020)
Ever since the concept of sustainable development first emerged, it has been assumed that this is the most important aspect of development policy at various levels of territorial organization, including at city level. Municipal waste management is one of the elements that has a significant impact on the broadly defined quality of life. The purpose of the article is to identify the barriers to the functioning of the Gdynia system in accordance with the principles of sustainable development. The pilot survey conducted as part of the study was targeted at residents, as they are the ones with the largest decision-making power in terms of how the waste management system will function. They included 18 statements divided into three sections: social, economic, and environmental. Attitude intensity was measured using a five-point Likert scale. The analysis and interpretation of the results helped identify the barriers to be overcome by residents if the city’s municipal waste management system is to meet the highest standards regarding sustainable development. In order to generalize and confirm the conclusions, the survey should be conducted on a larger sample
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 6, s. 76-86